GEOMICROBIOLOGY AND REDOX GEOCHEMISTRY OF THE KARSTIFIED MIOCENE GYPSUM AQUIFER, WESTERN UKRAINE: THE STUDY FROM ZOLOUSHKA CAVE - Andrejchuk V.N.; Klimchouk A.B. (My University, 2001)
The gypsum karst of the western Ukraine developed largely under artesian conditions. The Miocene aquifer is presently entrenched and dewatered over much of the territory, while it remains confined in the zone adjacent to the Carpathian Foredeep. The most prominent geochemical features of the Miocene aquifer system in the confined karst zone are: (1) the almost universal presence of a bioepigenetic calcite bed, enriched in the light carbon isotope, at the top of the gypsum (the "Ratynsky Limestone"), (2) the widespread sulfur mineralization associated with the above calcite bed (the region is one of the world's largest sulfur-bearing basins), and (3) high H2S and CO2 in the groundwater. Intense microbial sulfate-reduction processes occur in the gypsum in this zone. Zoloushka Cave is the third longest (92 km) and the largest by volume (more than 7 Г— 105 m3) gypsum cave in the world. It is a unique example of a young artesian cave that only during the Holocene became partly drained and during the last 50 years progressively dewatered due to a quarry operation. These rapid changes have induced a number of transitional geochemical processes, some of which appear to be bacterially mediated. Six groups of microorganisms have been identified in the cave. Our article discusses the aquifer geochemistry during the transitional stage in the light of the microbiological studies.
Keywords: Miocene; cave microbiology; gypsum aquifer hydrogeochemistry; iron hydroxides; manganese hydroxides; Zoloushka Cave; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен